2007
DOI: 10.1002/dir.20079
|View full text |Cite
|
Sign up to set email alerts
|

The impact of consumer Internet experience on channel preference and usage intentions across the different stages of the buying process

Abstract: We investigate consumer preference for online versus offline purchasing of a complex service (home mortgage), across the three stages of purchasing, namely, pre-purchase, purchase, and post-purchase. Our analysis of data from 300 consumers shows that (1) the offline channel is generally preferred over the online channel across all the stages, and (2) the channel usage intention in a particular stage is moderated by the consumer's Internet experience. Specifically, in both the pre- and post-purchase stages, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 50 publications
(65 reference statements)
9
150
0
4
Order By: Relevance
“…In order to understand how ZMOT, showrooming and webrooming shape the customer journey, interaction of customers across multiple channels needs to be examined. An empirical study by Frambach et al has demonstrated that 'the buying stage has an important influence on channel usage intention' 12 . Consumers seek different benefits at the pre-purchase stage than during or and after purchase.…”
Section: Theoretical Discussion -The Funnel Is Dead Long Live the Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand how ZMOT, showrooming and webrooming shape the customer journey, interaction of customers across multiple channels needs to be examined. An empirical study by Frambach et al has demonstrated that 'the buying stage has an important influence on channel usage intention' 12 . Consumers seek different benefits at the pre-purchase stage than during or and after purchase.…”
Section: Theoretical Discussion -The Funnel Is Dead Long Live the Loopmentioning
confidence: 99%
“…(2007) focused on the dichotomy of online-offline, such dualism is now largely outdated and the utilization of the growing number of channels by consumers is yet to be examined in the light of consumer decision-making 12 .…”
Section: Theoretical Discussion -The Funnel Is Dead Long Live the Loopmentioning
confidence: 99%
“…In the current studies [3][4][5][6][7], the consumer preference is frequently considered as one of the chief factors that influence the marketing. Especially, consumer's channel preference is a hot topic in supply chain research.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Vernik, Purohit, and Desai (2011) show that consumers may have strong preference for digital format in the music industry, and this preference can drive product sales. Frambach, Roest, and Krishnan (2007) demonstrate that consumers can develop higher preferences for the online purchasing channel when they have more favorable Internet experience. Our paper applies such existing concepts of consumers' brand awareness and channel preference to the setting of cross-channel effects between digital and physical channels.…”
Section: Literature Reviewmentioning
confidence: 93%